ANALISA FAKTOR-FAKTOR PENDORONG IMPLEMENTASI MANAJEMEN PERUBAHAN DALAM ORGANISASI STUDY KASUS PADA UMKM UD GEBAR SWEET DAIRY JOMBANG - Santosos, Rohmad Prio; Sanaji, Sanaji (ITB AAS Indonesia Surakarta, 2024)
This study aims to analyze the factors that drive the implementation of change management in organizations, with a focus on UD Gebar Sweet Milk MSMEs in Jombang. MSMEs have an important role in the local economy and overall economic growth. However, MSMEs often face challenges in managing change due to limited resources and managerial knowledge. This research uses a quantitative approach by studying all 25 employees. The results show that there are 2 new variables that affect the implementation of change management, namely internal external changes and managerial skills. The findings have important implications for owners, managers and local governments in developing strategies and policies that support successful change implementation in MSMEs. By implementing effective change management, MSMEs can better cope with change and strengthen their contribution to economic growth.